2012
DOI: 10.1097/bot.0b013e318216b1e5
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Negative Pressure Wound Therapy After High-Risk Lower Extremity Fractures

Abstract: There have been no studies evaluating incisional NPWT as a prophylactic treatment to prevent infection and wound dehiscence of high-risk surgical incisions. Our data demonstrate that there is a decreased incidence of wound dehiscence and total infections after high-risk fractures when patients have NPWT applied to their surgical incisions after closure. There is also a strong trend for decreases in acute infections after NPWT. Based on our data in this multicenter prospective randomized clinical trial, NPWT sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
297
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 325 publications
(315 citation statements)
references
References 34 publications
(48 reference statements)
8
297
0
7
Order By: Relevance
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies33, 36, 37, including that of B. D. Crist et al . (personal communication), used an NPWT device (VAC®) and six34, 35, 38, 39, including those of S. Karlakki et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations